Identification of six new lupane-type triterpenoids from Acanthopanax koreanum leaves and their tyrosinase inhibitory activities. Issue 3 (1st February 2016) - Dat, Le Duc; Thao, Nguyen Phuong; Luyen, Bui Thi Thuy; Tai, Bui Huu; Jeong, Min Hee; Woo, Mi Hee; Kim, Young Ho
Graphical abstract: Abstract: Chemical investigation of Acanthopanax koreanum leaves resulted in the isolation of 13 compounds (1 –13 ), including six new (20, 29)-dehydrolupane-type triterpenoids: 3α, 11α, 30-trihydroxylup-20(29)-en-23, 28-dioic acid (1 ), 3α, 11α, 30-trihydroxylup-20(29)-en-28-oic acid (2 ), 3α, 11α, 30-trihydroxylup-23-al-20(29)-en-28-oic acid (3 ), 3α, 11α-dihydroxy-20-oxo-30-norlupane-23, 28-dioic acid (5 ), (20 S )-3α-hydroxy-30 oxolupane-23, 28-dioic acid (8 ), (20 S )-3β, 7β, 29-trihydroxy-lupane-23-al-28-oic acid (10 ), and one novel compound isolated for the first time, named 3α, 20α, 29-trihydroxylupane-23, 28-dioic acid (9 ), together with six known compounds (4, 6, 7, and11 –13 ). Chemical structures of the isolated compounds were evaluated by analyzing and comparing spectroscopic data with those reported in the literature. These compounds were also evaluated for their tyrosinase inhibitory effects. Among them, compounds3, 7, 9, and12 showed significant inhibitory effects, with inhibitory concentrations of 50% (IC50 ) values ranging from 8.61 to 63.5 μM.